Literary Heritage or National Heritage? Landscape Preservation and Change in Dorset - Jones, Roy; Dolin, Timothy (Green Lines Instituto para o Desenvolvimento Sustentavel, 2012)
The largely rural landscape of Dorset is widely seen as being essentially and traditionally English. In part, this perception has been entrenched in the public mind by the late nineteenth and early twentieth century writings of Thomas Hardy and, in more recent years, by numerous film and television adaptations of his works. In an unrelated but in some ways parallel development, the Prince of Wales has encouraged the development of a present day version of a traditional English village at Poundbury on the outskirts of the county town of Dorchester (Hardy's Casterbridge). In this presentation, I argue that the surface features of past landscapes are often preserved or even recreated for contemporary purposes that have little to do with the (often agricultural) functions for which these landscape features were first devised and more to do with contemporary visions of heritage and even nationalism. This will be illustrated through the results of a survey of tourists at a variety of Hardy-related sites in and around Dorchester which considered the extent to which they sought and/or found rural landscapes which they could relate to Hardy's works. It will also consider the landscape of Poundbury, which has been developed as an idealisation of a traditional English village. Under the theme of heritage and sustainable development the paper will consider whether heritage(s) is/are being sustained, retained, transformed or creatively destroyed by literary tourism and royal property development in and around Dorchester.